2022
DOI: 10.1001/jamanetworkopen.2022.31778
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Immune Response After COVID-19 Booster Vaccination and Association With COVID-19 Omicron Infection

Abstract: IMPORTANCEThe BNT162b2 two-dose vaccine (BioNTech/Pfizer) has high effectiveness that wanes within several months. The third dose is effective in mounting a significant immune response, but its durability is unknown. OBJECTIVE To compare antibody waning after second and third doses and estimate the association of antibody kinetics with susceptibility to infection with the Omicron variant of SARS-CoV-2. DESIGN, SETTING, AND PARTICIPANTSIn a prospective longitudinal cohort study in a tertiary medical center in I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
57
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 29 publications
25
57
2
Order By: Relevance
“…Our findings that the higher durability of antibody titers after the 3-dose of mRNA vaccine than after 2-dose is consistent with a previous study of Israeli healthcare workers [3] and compatible with the effectiveness studies of mRNA vaccines showing a slower waning of VE for infection over time in recipients of 3-dose relative to those of 2-dose [15, 16]. In addition, we found that hybrid immunity (vaccination and infection) has added durability over the immunity induced by vaccination alone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings that the higher durability of antibody titers after the 3-dose of mRNA vaccine than after 2-dose is consistent with a previous study of Israeli healthcare workers [3] and compatible with the effectiveness studies of mRNA vaccines showing a slower waning of VE for infection over time in recipients of 3-dose relative to those of 2-dose [15, 16]. In addition, we found that hybrid immunity (vaccination and infection) has added durability over the immunity induced by vaccination alone.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological data are scarce regarding the waning pattern of humoral immunity following 2-and 3-dose COVID-19 vaccination and its related factors. Studies among 2-dose recipients showed that anti-SARS-CoV-2 spike antibody titers waned faster in older age [4] and female sex [3] and slower in those with a history of COVID-19 [5], but no such investigation has been done for 3-dose. It remains elusive for both doses whether the waning speed of antibody differs depending on obesity [6,7], comorbid conditions [7,8], immunosuppression [7,8], or behavioral factors (smoking and alcohol drinking [9][10][11]), which have been linked to lower immune response to COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that the AT50 of IgG and N-Ab responses were longer following the third dose than after the second dose. Other studies [ 18 ] have also demonstrated a similar pattern where waning of both IgG and N-Ab was slower after the third compared to the second dose (IgG 1.32% vs. 2.26% per day and N-Ab 1.32% vs. 3.34% per day). Given that total S-Ab exhibited a shorter AT50 than IgG post-booster, both antibody levels may need to be assessed to observe the waning antibody levels post-vaccination, and IgG may be the preferred antibody to follow-up for long-term antibody response.…”
Section: Discussionsupporting
confidence: 62%
“…The comparison between the results of our previous report and our current study after the first booster dose led to an inference that the original monovalent vaccine rapidly loses immunity against Omicron (10). This inference conforms with reports based on similar studies (14, 19). In fact, vaccine effectiveness waned remarkably within a few months of administration in clinical settings (20, 21).…”
Section: Discussionsupporting
confidence: 94%